Exogenous leptin affects sperm parameters and impairs blood testis barrier integrity in adult male mice - Xiaotong Wang; Xiaoke Zhang; Lian Hu; Honggang Li (BMC, 2018)
Abstract Background Serum leptin levels are augmented in obese infertile men and in men with azoospermia. They also correlate inversely with sperm concentration, motility and normal forms. The mechanisms underlying the adverse effects of excess leptin on male reproductive function remain unclear. The present study aimed to evaluate the effects of exogenous leptin on sperm parameters in mice and to explore the underlying mechanisms. Methods We treated normal adult male mice with saline, 0.1, 0.5 or 3 mg/kg leptin daily for 2 weeks. After treatment, serum leptin levels, serum testosterone levels, sperm parameters and testicular cell apoptosis were evaluated. Blood testis barrier integrity and the expression of tight junction-associated proteins in testes were also assessed. We further verified the direct effects of leptin on tight junction-associated proteins in Sertoli cells and the possible leptin signaling pathways involved in this process. Results After treatment, there were no significant differences in body weights, reproductive organ weights, serum leptin levels and serum testosterone levels between leptin-treated mice and control mice. Administration of 3 mg/kg leptin reduced sperm concentration, motility and progressive motility while increasing the percentage of abnormal sperm and testicular cell apoptosis. Mice treated with 3 mg/kg leptin also had impaired blood testis barrier integrity, which was related to decreased tight junction-associated proteins in testes. Leptin directly reduced tight junction-associated proteins in Sertoli cells, JAK2/STAT, PI3K and ERK pathways were suggested to be involved in this process. Conclusions Exogenous leptin negatively affects sperm parameters and impairs blood testis barrier integrity in mice. Leptin reduced tight junction-associated proteins in Sertoli cells, indicating that leptin has a direct role in impairing blood testis barrier integrity. Given the function of blood testis barrier in maintaining normal spermatogenesis, leptin-induced blood testis barrier impairment may be one of the mechanisms contributing to male subfertility and infertility.